A Common Language: How Neuroimmunological Cross Talk Regulates Adult Hippocampal Neurogenesis - Odette Leiter; Gerd Kempermann; Tara L. Walker (Hindawi Limited, 2016)
Immune regulation of the brain is generally studied in the context of injury or disease. Less is known about how the immune system regulates the brain during normal brain function. Recent work has redefined the field of neuroimmunology and, as long as their recruitment and activation are well regulated, immune cells are now known to have protective properties within the central nervous system in maintaining brain health. Adult neurogenesis, the process of new neuron generation in the adult brain, is highly plastic and regulated by diverse extrinsic and intrinsic cues. Emerging research has shown that immune cells and their secreted factors can influence adult neurogenesis, both under baseline conditions and during conditions known to change neurogenesis levels, such as aging and learning in an enriched environment. This review will discuss how, under nonpathological conditions, the immune system can interact with the neural stem cells to regulate adult neurogenesis with particular focus on the hippocampus-a region crucial for learning and memory.